Isolation, Characterization and Identification of Lipase-Producing Bacteria from Olive Oil Mills Wastes - Seda Nur Gelir; Zehra Burcu Bakır (Turkish Journal of Agriculture: Food Science and Technology, 2025)
This study aimed to utilize waste products while identifying bacteria capable of producing the industrially significant enzyme lipase. The research investigated the potential of olive oil production waste obtained from an olive oil factory in Aydın Province in Turkey as a source of novel bacterial isolates with lipase-producing capabilities. During the study, samples obtained from olive oil mills wastes were enriched in liquid media and subsequently cultured on tributyrin agar. Colonies exhibiting lipase activity were selected and subjected to quantitative assays for lipase activity. Following this, DNA isolation was conducted, and the molecular identification of the selected strains was performed using 16S rRNA analysis. A total of 14 bacterial isolates with distinct colony morphologies and lipase production capabilities were identified in the study. Of these, nine isolates were obtained from olive mill wastewater (OMW), while five were isolated from olive pomace samples. The lipase activity of the isolates was measured in triplicate. The results indicated that isolates L0918 and L0919 exhibited significantly higher activity values, with 137.39 U/mL and 62.76 U/mL, respectively, compared to the other isolates. BLAST analysis revealed that isolate L0918 shared 99% similarity with Serratia sp., while isolate L0919 demonstrated 98% similarity with Serratia liquefaciens. The findings of this study suggest that olive oil mill byproducts have significant potential as a source of diverse bacteria capable of producing the industrially important enzyme lipase. Additionally, these byproducts can be effectively utilized as a growth medium for such bacterial strains.